The Impact of Higher Secondary ICT Education on University STEM Student Performance - Khalid Been Badruzzaman Biplob; Mohd Azman Hashim; Mohamed Emran Hossain; Abu Kowshir Bitto; Syed Najihuddin Syed Hassan; Most.Nahida Sultana (Emerging Science Journal, 2025)
This study investigates the significant impact of ICT education from the Higher Secondary Certificate (HSC) on Bangladeshi students' progress in tertiary STEM fields. Through utilizing a comprehensive examination of demographic profiles, proficiency assessments, facility rating systems, and satisfaction measures, this study determines the complex relationships between HSC-level ICT education as well as success in STEM areas at the university level. Data were collected through an online survey from 244 students enrolled in Computer Science and Engineering (CSE), Software Engineering (SWE), and Information Technology Management (ITM) departments. The results highlight how many different factors have significant effects on students' first-semester SGPA. Several variables, including prior ICT knowledge on data handling from college, quality of instruction provided by the college ICT teacher, and HSC-level ICT course grade, have strong relationships with student performance at the university level. This study illustrates the positive impact of improved instructional materials and teacher-led projects on strong skill development, a phenomenon that will increase overall satisfaction among learners. Although geographical location, gender, and college type have been explored, it does not appear that they have significantly affected ICT course grades directly. Instead, instructional components and techniques for improving skills become important factors in determining students' academic performance. The study not only finds significant relationships but also promotes curriculum improvements with a focus towards ICT education technique optimization. With an aim of improving instructional methods and curriculum design, these observations provide governments and other individuals within education with suggestions that are applicable. The study highlights how important it is to effectively utilize ICT education in order to encourage overall STEM development in Bangladesh's educational system.